Effects of repetitive practice of motor tasks on somatosensory gating - Akaiwa, Mayu; Matsuda, Yuya; Saito, Hidekazu; Shibata, Eriko; Sasaki, Takeshi; Sugawara, Kazuhiro (Frontiers in Human Neuroscience, 2023)
Introduction During voluntary muscle contraction, the amplitude of the somatosensory evoked potential (SEP) is reduced by inhibiting sensory information from a peripheral nerve supplying the contracted muscle. This phenomenon is called “gating.” We reported that participants with good motor skills indicated strong suppression of somatosensory information. The present study investigated the effects of motor performance improvement following repetitive practice on the SEP amplitude. Methods The ball rotation task (BR task) was practiced by 15 healthy participants repetitively. SEPs were recorded before (pre) and after (post) repetitive practice. Results The BR task performance was significantly improved and the required muscle activation to perform the task was significantly reduced after the repetitive practice. The degree of gating was not significant between pre and post- for the SEP amplitude. A significant correlation was found between changes in SEP amplitude from pre to post and performance improvement. Discussion After repetitive practice, the degree of gating did not change, but the performance of the BR task improved, and the muscle activity required for the BR task decreased. These results suggest that repetitive practice does not change the degree of gating but changes the mechanism of gating. Furthermore, they indicate that suppression of the somatosensory area may play a role in improving task performance.